Fusion genes in high-grade serous ovarian cancer - Rausio, Heidi (fi=Turun yliopisto|en=University of Turku|, 2023)
High-grade serous ovarian cancer (HGSC) is the most common and lethal subtype of ovarian cancer. Debulking surgery is the primary treatment, supplemented by platinum and taxane combination chemotherapy. The response to treatment is generally good, but most patients eventually develop drug resistance, leading to disease progression and death. Nevertheless, the treatment strategy has remained relatively unchanged, and overall survival has hardly improved over the last 20 years. The primary events in early HGSC development are the inactivation of the tumor suppressor p53, and the homologous recombination pathway, which results in a severely damaged genome and allows the development of individual cancer cell clones. Genomic rearrangements, including gene fusions may evolve, when two separate genes join to form a new gene product. Genes can also fuse at the RNA level due to splicing. The functional changes in fusion proteins and chimeric RNAs can cause cancer initiation, tumor progression, and drug resistance. HGSC is a genetically unstable disease in which fusions are very common. Poor treatment outcomes can be associated with the emergence of treatment-resistant subclones. Deep sequencing has significantly increased the knowledge of the molecular characteristics of HGSC. Understanding the genomic and non-genomic abnormalities of HGSC tumors will help design personalized therapeutic approaches and discover novel mechanisms of drug resistance. However, at present, the role of gene fusions in HGSC is poorly studied. This Ph.D. thesis aimed to identify new potential drug targets for ovarian cancer patients. Using computational modeling, we identified 228 novel fusion genes from 107 cancer samples of 36 HGSC patients. We demonstrated by laboratory experiments the presence of the most biologically interesting fusions in cancer cells. Furthermore, we investigated the PIK3R1-CCDC178 fusion protein and its role as a tumor-promoting alteration and impact on drug response. The fusion induced HGSC cell migration and resistance to platinum and trametinib treatment through ERK1/2 activation but the fusion-expressing cells remained sensitive to the combination of the treatments. Therapy resistance was associated with rod and ring-like cellular structure formation.

Fuusiogeenit huonosti erilaistuneessa seroosissa munasarjasyövässä Huonosti erilaistunut seroosi munasarjasyöpä (HGSC) on yleisin ja tappavin munasarjasyövän muoto. Perushoitomuoto on leikkaus, jota täydennetään platinan ja taksaanin yhdistelmähoidolla. Hoitovaste on usein hyvä, mutta suurimmalle osalle potilaista kehittyy lääkeresistenssi, mikä johtaa syövän etenemiseen ja kuolemaan. Hoitostrategia on pysynyt melko muuttumattomana eikä potilaiden kokonaiselossaoloajassa ole tapahtunut juurikaan edistystä viimeisten 20 vuoden aikana. HGSC:n alkuvaiheessa p53-kasvunrajoiteproteiinin sekä homologisen rekombinaatiokorjausreitin toimimattomuus johtavat vaikeasti vioittuneeseen genomiin ja mahdollistavat yksilöllisten syöpäsolukloonien kehittymisen. Geenifuusiot voivat syntyä genomin uudelleenjärjestäytymisen seurauksena, jolloin kaksi erillistä geeniä muodostavat uuden geenituotteen. Geenit voivat fuusioitua myös RNA-tasolla silmukoitumisen seurauksena. Fuusioproteiinien ja -RNA:iden toiminnalliset muutokset voivat edesauttaa syövän syntymistä, etenemistä sekä lääkeresistenssin kehittymistä. HGSC on geneettisesti hyvin epävakaa tauti, jossa fuusiot ovat erittäin yleisiä. Huono hoitotulos voidaan yhdistää hoitoresistenttien alakloonien syntymiseen. Syväsekvensointi on lisännyt merkittävästi tietoa HGSC:n molekulaarisista ominaisuuksista. Kasvainten genomisten ja ei-genomisten poikkeavuuksien ymmärtäminen auttaa yksilöllisten terapeuttisten ratkaisujen suunnittelussa ja uusien lääkeresistenssimekanismien löytämisessä. Toistaiseksi geenifuusioiden merkitystä HGSC:ssä on tutkittu melko vähän. Väitöskirjatutkimukseni tarkoituksena oli löytää uusia potentiaalisia syöpälääkekohteita munasarjasyöpäpotilaille. Tunnistimme 228 uutta fuusiogeeniä 36:n HGSCpotilaan 107:sta syöpänäytteestä tietokonemallinnusta hyödyntäen. Osoitimme laboratoriokokein biologisesti mielenkiintoisimpien fuusioiden olemassaolon syöpäsoluissa. Tutkimme tarkemmin PIK3R1-CCDC178 fuusioproteiinin biologiaa ylituottosoluissa. Fuusio aikaansai ERK1/2 viestireitin aktivaation ja indusoi HGSCsolujen migraatiota ja resistenssin platina- ja trametinibihoidolle. Solut olivat kuitenkin herkkiä yhdistelmähoidolle. Lääkeresistenssi liittyi sauvamaisten ja rengasmaisten solunsisäisten filamenttirakenteiden muodostumiseen.